Predictors of dropout among adolescents with borderline personality disorder attending mentalization-based group treatment. (3rd October 2021) - Jørgensen, Mie Sedoc; Bo, Sune; Vestergaard, Martin; Storebø, Ole Jakob; Sharp, Carla; Simonsen, Erik
Abstract: Background: Premature termination from treatment or dropout is prevalent among patients with borderline personality disorder (BPD). To our knowledge, no studies have examined which factors predisposes dropout from therapy among adolescents with BPD. The current study examined sociodemographic, clinical and psychological predictors of dropout among adolescents who attended a one-year treatment program with mentalization-based group treatment (MBT-G). Methods: Participants were 89 female adolescent patients aged 14–18 years who attended MBT-G in a Danish child and adolescent psychiatric service and 56 matched controls who received non-manualized individual sessions (treatment as usual). Forty (45%) dropped out and 49 (55%) completed treatment in MBT-G. Pretreatment predictors included (1) sociodemographic variables such as age, schooling, relationship status and after-school job, (2) clinical measures of self-reported adolescent borderline personality features, depression, self-harm, internalizing and externalizing symptoms, and (3) psychological measures on self-reported reflective functioning (i.e., mentalizing) and attachment to peers and parents. Results: Binary logistic regression analyses revealed that lower reflective functioning was the only significant predictor of dropout in MBT-G. No sociodemographic or clinical variables predicted dropout. No significant predictors of dropout were identified among participants who received treatment as usual. Conclusions: Adolescents with BPD who report low reflective functioning are at increased risk of dropping out of MBT-G treatment but not treatment as usual. These findings highlight that clinicians need to consider level of reflective functioning among adolescents with BPD in MBT or in group therapy and adapt psychotherapy to the needs of the patient in order to reduce dropout.